Brazilian generics market change after Farmácia Popular program - Andréa Dâmaso Bertoldi; Luisa Arueira Chaves; Dennis Ross-Degnan; Vera Lucia Luiza; Isabel Cristina Martins Emmerick; Rondineli Mendes da Silva; Mônica Rodrigues Campos (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To evaluate trends in the use of generic and non-generic medicines to treat hypertension and diabetes under the Farmácia Popular Program (FP) and its impact on generic medicines sales volume and market share in the Brazilian pharmaceutical market. METHODS This longitudinal, retrospective study used interrupted time series design to analyze changes in monthly sales volume and proportion of medicines sales (market share) for oral antidiabetic and antihypertensive medicines for generic versus non-generic products. Analyses were conducted in a combined dataset that aggregate monthly sales volumes from the Farmácia Popular program and from the QuintilesIMS™ (IQVIA) national market sales data from January 2007 to December 2012. The Farmácia Popular program phases analyzed included: a) 2009 reductions in medicines reference prices (AFP-II) and b) 2011 implementation of free medicines program for hypertension and diabetes, the Saúde não tem preço (SNTP - Health has no price). RESULTS Patterns of use for FP-covered antidiabetic and antihypertensive medicines were similar to their use in the market in general. After one year of the decreases in government subsidies in April 2010, market share of antidiabetic and antihypertensive medicines experienced relative declines of -54.5% and -59.9%, respectively. However, when FP-covered medicines were made free to patients, overall market volume for antidiabetic and antihypertensive generics increased dramatically, with 242.6% and 277.0% relative increases by February 2012, as well as non-generics with relative increase of 209.7% and 279% for antidiabetic and antihypertensive medicines, respectively. CONCLUSIONS Ministry of Health policies on the amount of patient cost sharing and on the choice of medicines on coverage lists have substantial impacts on overall generic sales volume in retail pharmacies.